ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Yayan Amri Wijaya, 08.05.52.0063; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2013)
Purpose of this study was to tested the effect of Quality Audit, Audit Opinion, and Audit Lag on Opinion Audit Going Concern acceptance of the manufacturing companies located in Indonesian Stock Exchange of financial statement to make decisisonscorrectly.The auditor is also responsible for assessing whether period of not more than one year from the date of the audit report. In this research, the research using purposive sampling and obtained a sample of 39 manufacturing companies listed on the Indonesian Stock Exchange in 2008 - 2010. The method of analysis used was logistic regression. The results of this research indicate Quality Audit and Audit Lag no effect on acceptance Audit Opinion Going Concern and the Audit Opinion The Previous Year influence on acceptence Audit Opinion Going Concern. This research has the limitations of the limited 5 years study period, so not ideal to see the trend of the effect of financial conditions. Variables research usinf 3 independentvariables namely Quality Audit, Audit Opinion The Previous Year, and Audit Lag as wellas a dependent variable that is Audit Opinion Going Concern. This research used data only manufacturing companyKeywords: Going Concern, The Quality Of The Audit, The Audit Opinion The Previous Year, Audit Lag.